Analisis Yuridis Agresi Israel Di Palestina Perspektif Hukum Pidana Internasional Dan Hukum Pidana Islam Terkait Sanksi Genosida Dalam Statuta Roma Bagian 7 No. 77 Tahun 1998 - Joli, Angelika; Kholid, Muhammad; Royani, Yayan Muhammad (Maqasid: Jurnal Studi Hukum Islam, 2025)
The prolonged and systematic aggression by Israel against Palestine has sparked urgent debates in the fields of international criminal law and Islamic criminal law. This study seeks to examine the issue of whether the acts committed by Israel against Palestinian civilians constitute genocide, analyzed from both perspectives. The objective is to explore the legal classification, the elements of the crime, and the applicable sanctions from international and Islamic frameworks. This research adopts a normative juridical approach using conceptual, statutory, and comparative methods. The study analyzes primary and secondary legal sources to construct a comprehensive understanding of the crime’s legal dimensions. Findings indicate that the aggression fulfills essential criteria of genocide, particularly concerning intent, systematic targeting of civilians, and the scale of destruction. From the Islamic perspective, the acts also correspond to grave offenses that endanger life, dignity, and communal safety. Both legal systems emphasize the protection of life and impose severe sanctions for crimes of such magnitude. This study underscores the need for integrated global legal accountability that aligns universal values with religious justice. Keywords: Genocide Prosecution, Israeli Aggression, Islamic Criminal Law, International Criminal Justice, Palestine Conflict